Comparison of permanent pacemaker implantation rate after first and second generation of transcatheter aortic valve implantation–A retrospective cohort study. Issue 7 (4th August 2021) - Minha, Sa'ar; Yarkoni, Yuval; Segev, Amit; Finkelstein, Ariel; Danenberg, Haim; Fefer, Paul; Orvin, Katia; Steinvil, Arie; Maor, Elad; Beinart, Roy; Rosso, Raphael; Golovchiner, Gregory; et al.
Abstract: Objectives: This study aimed to compare permanent pacemaker implantation (PPMI) rates among patients undergoing Trans‐catheter Aortic Valve Implantation (TAVI) with first generation (G1) versus second generation (G2) valves and the impact of PPMI on long‐term mortality. Background: PPMI is a known adverse event after TAVI. Recently, two novel iterations of valve designs of both the balloon expandable valves (BEV) and self‐expanding valves (SEV) were introduced as a second generation valves. Methods: All patients included in the Israeli multicenter TAVI registry were grouped according to valve type (BEV vs. SEV) and generation (G1 vs. G2). A comparison was made for clinical and outcome indices of patients undergoing TAVI with G1 and G2 in each of the valve systems. Results: A total of 1377 patients were included. The incidence of PPMI did not differ between G1‐BEV versus G2‐BEV (15.3% vs. 17.4%; p  = 0.598) nor between G1‐SEV versus G2‐SEV (23.4% vs. 20.3%; p  = 0.302). Depth of implantation and complete right bundle branch block were independently associated with PPMI post‐TAVI in both valve systems. PPMI was not associated with an increased risk for 2‐year mortality. Conclusions: The incidence of PPMI remains a relevant adverse event post‐TAVI even when the newer generation valves are used. Since the predictors for PPMI are well established, a standardized approach for the management of conduction disorders is much needed.